Does window-to-wall ratio have a significant effect on the energy consumption of buildings? A parametric analysis in Italian climate conditions. (September 2017) - Marino, C.; Nucara, A.; Pietrafesa, M.
Abstract: Building envelope structures play a pivotal role in the energy behavior of edifices. They influence the heat exchanges between indoor and outdoor environment and might allow a proper exploitation of solar energy. Therefore, when properly designed, they can contribute to minimizing the overall energy demand of buildings, allowing achievement of the high energy performance that is the basis of the Nearly Zero Energy Building (NZEB) concept. In this context, window systems are generally considered as the crucial element to be correctly designed for energy efficiency purposes in view of the role they play in heat exchange processes and solar gain management. This paper outlines the methodology and the correspondent results of an analysis which aims to search for the optimal size of the window surface, which is the size allowing minimum overall energy consumption, in an office building whose structure and configuration represent a typical reference case for the Italian building stock. Several configurations were considered, varying the climate, the thermal features of the building envelope and the installed lighting electric power. Furthermore, the influence of a switchable shading device was assessed and the correlated comfort consideration reported. The analyses were performed using Energy Plus simulation code and the window dimensions were evaluated in terms of the ratio between the glazed surface and the gross façade area, which is referred to as window to wall ratio (WWR). Highlights: Integrated energy simulations of a reference building were performed. Optimal values of WWR able to minimize overall consumptions were searched. Influence of façade features, climate, luminaries characteristics was investigated. Influence of a smart switchable shading device was also analyzed. Results provide suitable hints about window design and building energy efficiency.